Anti-proliferation of MDA-MB-231 cells by Averrhoa bilimbi extract is associated with G0/G1 perturbation and mitochondria-mediated apoptosis independent of p53 - Yan, See Wan; Rahmat, Asmah (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2017)
Practiced as folk medicine since ancient times, bilimbi (Averrhoa bilimbi) is commonly consumed and widely cultivated in Malaysia. In search for naturally occurring anticancer agents, a potential fruit extract was found to exert anticancer properties in vitro without any cytotoxic effect on normal cells. This study investigated the anti-proliferative effect and underlying cell death pathway induced by bilimbi ethanolic extract on human non-hormone-dependent breast cancer cell line, MDA-MB-231. Anticancer potential of bilimbi extract was conducted by investigating the in vitro growth inhibitory effect, DNA fragmentation, cell cycle progression and anti-proliferation assay. Release of caspases, cytochrome c and apoptotic proteins were demonstrated to determine the mechanism of cell death pathway. Findings revealed that bilimbi inhibited growth of MDA-MB-231 cells through the induction of apoptosis mediated by cell cycle arrest at G0/G1 checkpoint. Released of cytochrome c coupled with up-regulation of caspase-3/7, caspase-9 and Bax pro-apoptotic proteins in addition to down-regulation of dysfunctional p53 and Bcl-2 anti-apoptotic proteins implied that bilimbi induced a p53-independent mitochondrial apoptosis pathway in MDA-MB-231. These results suggest that bilimbi could induce tumor cell anti-proliferation through apoptosis. As a natural product, bilimbi could be a promising anticancer agent and an inexpensive approach to cancer chemoprevention strategy.